Peran Notaris Sebagai Pejabat Umum Dalam Era Revolusi Industri 4.0 - Dista Vennesya Mirna Talita; Edith Ratna (Program Studi Magister Kenotariatan, Fakultas Hukum, Universitas Diponegoro, 2023)
AbstractA notary is a public official who has the authority to make an authentic. Notaries have an obligation to keep up with the times that have a relationship with the notary. The era of the Industrial Revolution 4.0 was the beginning of the merger between automation technology and cyber technology. The purpose of this study is to determine the role of the notary as a general official in the era of the industrial revolution 4.0 and the responsibility of the notary as a general official in the era of the industrial revolution 4.0. The research method used is normative juridical. The results of this study were found that the role of the notary in providing support for government regulations to serve the process of licensing integrity with electronic (OSS), efforts to arrange business entities according to KBLI until the business entity has NIB. It is expected that the notary in the era of the Industrial Revolution 4.0 can be open to digitalization but without ignoring the duties and obligations of the Notary. The notary is responsible for the formal form of authentic deed in accordance with the law and must be careful so that there is no legal flaw. Keyword: notary; notary role; industry revolution 4.0AbstrakNotaris ialah pejabat umum yang memiliki wewenang dalam pembuatan akta otentik. Notaris memiliki kewajiban untuk mengikuti perkembangan zaman yang memiliki keterkaitan mengenai hubungan yang terkait dengan Notaris. Era Revolusi Industri 4.0 merupakan awal dari penggabungan antara teknologi otomatisasi dengan teknologi siber. Tujuan penelitian ini untuk mengetahui peran Notaris sebagai pejabat umum di era Revolusi Industri 4.0 dan tanggung jawab Notaris sebagai pejabat umum dalam era Revolusi Industri 4.0. Metode penelitian yang digunakan adalah Yuridis Normatif. Hasil penelitian ini didapatkan bahwa peran Notaris dalam memberi dukungan peraturan pemerintah untuk melayani proses perizinan terintegritasi dengan elektronik (OSS), upaya penataan badan usaha menurut KBLI hingga badan usaha tersebut memiliki NIB. Diharapkan notaris dalam era Revolusi Industri 4.0 ini dapat terbuka terhadap digitalisasi namun tanpa mengesampingkan tugas dan kewajiban Profesi Notaris. Notaris bertanggung jawab pada bentuk formal akta otentik sesuai undang-undang dan harus hati-hati agar tak ada cacat hukum.Kata kunci: notaris, peran notaris, revolusi industry 4.0